A Regulatory Role of NAD Redox Status on Flavin Cofactor Homeostasis in S. cerevisiae Mitochondria. (1st September 2013) - Giancaspero, Teresa Anna; Locato, Vittoria; Barile, Maria
Abstract : Flavin adenine dinucleotide (FAD) and nicotinamide adenine dinucleotide (NAD) are two redox cofactors of pivotal importance for mitochondrial functionality and cellular redox balance. Despite their relevance, the mechanism by which intramitochondrial NAD(H) and FAD levels are maintained remains quite unclear in Saccharomyces cerevisiae . We investigated here the ability of isolated mitochondria to degrade externally added FAD and NAD (in both its reduced and oxidized forms). A set of kinetic experiments demonstrated that mitochondrial FAD and NAD(H) destroying enzymes are different from each other and from the already characterized NUDIX hydrolases. We studied here, in some detail, FAD pyrophosphatase (EC 3.6.1.18), which is inhibited by NAD + and NADH according to a noncompetitive inhibition, with K i values that differ from each other by an order of magnitude. These findings, together with the ability of mitochondrial FAD pyrophosphatase to metabolize endogenous FAD, presumably deriving from mitochondrial holoflavoproteins destined to degradation, allow for proposing a novel possible role of mitochondrial NAD redox status in regulating FAD homeostasis and/or flavoprotein degradation in S. cerevisiae .